2004
DOI: 10.1213/01.ane.0000099782.78002.30
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Phenylephrine Infusion for Preventing Hypotension During Spinal Anesthesia for Cesarean Delivery

Abstract: In patients receiving spinal anesthesia for elective cesarean delivery, a prophylactic infusion of phenylephrine 100 microg/min decreased the incidence, frequency, and magnitude of hypotension with equivalent neonatal outcome compared with a control group receiving IV bolus phenylephrine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(75 citation statements)
references
References 24 publications
5
68
1
1
Order By: Relevance
“…These haemodynamic effects or findings are in agreement with other studies [8,10,11] indicating that phenylephrine administered as infusion effectively maintains SBP, MAP and DBP, but decreases heart rate during spinal anaesthesia and CSE. NganKee and colleagues [12] demonstrated that in patients receiving spinal anaesthesia for Caesarean section, a prophylactic infusion of phenylephrine 100 μg/min given immediately after initiation of spinal block decreased the incidence, frequency and magnitude of hypotension compared with a control group receiving intravenous bolus of 100 μg phenylephrine given as treatment for episodes of hypotension. The lower dose of phenylephrine used in this study was to ensure a relative potency of 80:1 based on the study by Saravanet al [13].…”
Section: Discussionmentioning
confidence: 99%
“…These haemodynamic effects or findings are in agreement with other studies [8,10,11] indicating that phenylephrine administered as infusion effectively maintains SBP, MAP and DBP, but decreases heart rate during spinal anaesthesia and CSE. NganKee and colleagues [12] demonstrated that in patients receiving spinal anaesthesia for Caesarean section, a prophylactic infusion of phenylephrine 100 μg/min given immediately after initiation of spinal block decreased the incidence, frequency and magnitude of hypotension compared with a control group receiving intravenous bolus of 100 μg phenylephrine given as treatment for episodes of hypotension. The lower dose of phenylephrine used in this study was to ensure a relative potency of 80:1 based on the study by Saravanet al [13].…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary articles emphasize on the arterial rather than venous circulation and project the reduced systemic vascular resistance as the primary factor for the genesis of maternal hypotension [6][7][8] . Over the last few years, there is a trend to rely more on vasopressors than either crystalloid or colloid alone 4,6,7 .…”
Section: Issn: 0975-8232mentioning
confidence: 99%
“…Different vasopressors are commonly used at present with varying degrees of success 6 . Despite the use of prophylactic intravenous (i.v.)…”
Section: Issn: 0975-8232mentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, when severe and sustained, hypotension can impair uterine and intervillous blood flow and ultimately result in fetal acidosis and neonatal depression [1][2][3][4]. Prevention measures include fluid preload, left lateral tilt, and use of vasopressors [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%